19 A large, multicenter, retrospective study on efficacy and safety of stereotactic body radiotherapy (SBRT) in oligometastatic ovarian cancer (MITO RT1 study). (18th September 2019) - Macchia, G; Lazzari, R; Colombo, N; Laliscia, C; Capelli, G; D'Agostino, GR; Deodato, F; Trippa, F; Ippolito, E; Ronchi, S; Pajar, F; Scorsetti, M; et al.
Abstract : Objectives: The aim of this retrospective, multicenter study (MITO RT-01) was to define activity and safety of Stereotactic Body Radiotherapy (SBRT) in a very large, real life dataset of metastatic/persistent/recurrent ovarian cancer (MPR-OC) patients. Clinical and SBRT parameters have been analyzed in order to identify predictors of outcome. Methods: The endpoints of the study were the rate of complete response (CR) to SBRT, and the 24-month actuarial local control (LC) rate on "per lesion" basis. The secondary end-points were acute and late toxicities, and the 24-month actuarial late toxicity free survival. Toxicity was evaluated by RTOG/EORTC and CTC-AE scales, according to center policy. Logistic and Cox regression were used for the uni- and multivariate analysis of factors predicting clinical CR and actuarial outcomes. Results: CR, PR and SD were observed in 291 (65.2%), 106 (23.8%), and 33 (7.4%) lesions. Patient age <60 years, PTV <18 cm3, lymph node disease, and BEDα/β10 >70 Gy were associated with higher chance of CR in the multivariate analysis. With a median follow-up of 22 months (range: 3–120), the 24-month actuarial LC rate was 81.9%. Achievement of CR and total dose >25 Gy were associated with better LC rate in the multivariate analysis. Mild toxicity was experienced in 54 (20.7%) patients. The 24- month late toxicity free survival rate was 95.1%. Conclusions: This study confirms the activity and safety of SBRT in MPR-OC patients and identifies clinical and treatment parameters able to predict CR and LC rate.